Effects of Dietary Mannan-Oligosaccharide (Mos) and Multi-Species of Bacillus on Growth and Feed Utilization in Leopard Coral Grouper Plectropomus leopardus Juvenile - Sudewi Sudewi; Ni Wayan Widya Astuti; Yasmina Nirmala Asih; Afifah Nasukha; Muhammad Marzuqi; Indah Mastuti; Ketut Mahardika; Sari Budi Moria Sembiring; I Nyoman Adiasmara Giri (Bogor Agricultural University, Indonesia, 2023)
This study assessed the growth and feed utilization in leopard coral grouper Plectropomus leopardus juvenile fed dietary prebiotic mannan-oligosaccharide (MOS) and multi-species of probiotic bacteria (Bacillus cereus BS6, B. subtilis BS3, and B. amiloliquefaciens BS4). The experiment was performed by feeding four replicates groups of juveniles weighing 3.61±0.60 g on four experimental diets, and each diet included: only MOS (PRE); the multi-species of Bacillus (PRO); a combination of MOS and the multi-species of Bacillus (SYN) and without supplementation (CON). When MOS (PRE) or the multi-species of Bacillus (PRO) was included in the diet solely, the growth of the fish was fairly good, although there was no significant difference with the control diet (p>0.05). Unexpectedly, the combined inclusion of MOS and the multi-species of Bacillus (SYN) did not increase the growth and feed utilization in Plectropomus leopardus juvenile. Presumably, MOS did not exert any favorable effects on the multi-species of Bacillus. This study suggested that no advantage was obtained when MOS and the multi-species of Bacillus were included in the diet simultaneously. In addition, the inclusion of MOS in higher levels may be necessary for better feed utilization and growth in leopard coral grouper Plectropomus leopardus.